Analysis of culturable bacteria from soil of three sites on anchorage island, Antarctic Peninsula - Maryam, Karimian (2011)
Since soil-borne bacteria represent the world's greatest source of biological diversity, the diversity of culturable bacteria associated with soil from three different regions of the Anchorage Island on the Antarctic Peninsula was investigated. Soil samples analysed included Sandy coarse soil (AI1), Black & fine soil (AI2) and High nutrient (AI3). A total of 196 bacteria were isolated under aerobic conditions at 4°C using Nutrient agar as medium. The isolates were grouped using morphology and amplified rRNA gene restriction analysis fingerprinting and identified by partial sequencing of 16S rRNA gene. Out of 14 different RFLP patterns and different morphologies that were sequenced, bacterial isolates fell in four phylogenetic groups: Actinobacteria, Bacteroidetes, subclasses α, ß, and γ-Proteobacteria and Deinococcus. Actinobacteria phylum contained Arthrobacter, Rhodococcus and Agreia was dominated in all samples (57%) especially in AI2 with more than 90%. Flavobacterium, Sejongia and Chryseobacterium from Bacteroidetes were dominant after Actinobacteria with 20.3%. Proteobacteria phylum contains Sphingomonas, Polaromonas, Naxibacter, Janthinobacterium, Peseudomonas and Psychrobacter with 15.1% was third phylum that isolated among all samples. While α-Proteobacteria were isolated from AI2 and AI3 samples, whereas ß Proteobacteria and γ- Proteobacteria were found in AI1 and AI3 samples. Deinococcus phylum with 7.6% was isolated in AI3 sample. Totally based on phylogenetic trees, at least 24 different genera were identified. Dependent upon sequence analysis (<96% sequence similarity), the Anchorage Island isolates belonged to at least 13 different bacterial families. These results indicated a high culturable diversity within the bacterial community of the Anchorage Island soil samples.